Historical and future heat-related mortality in Portugal’s Alentejo region - Dora Neto; Miguel Bastos Araújo (BMC Public Health)
Abstract Background The increased severity of extreme weather and anticipated climate change has intensified heat stress-related mortality worldwide. This study examines the historical short-term effects of heat on mortality in Alentejo, Portugal’s warmest region, and projects it up to the end of the century. Methods Using data from 1980 to 2015 during warm seasons (May-September), the association between daily mortality by all-causes and mean temperature was examined following a case time series design, applied at both regional and subregional scales. Projections for daily temperatures were obtained from regional climate models and greenhouse gas emission scenarios (RCP4.5, RCP8.5). We also examined temporal shifts in mortality considering potential long-term and seasonal adaptative responses to heat. We then quantified the yearly effects of heat by calculating absolute and relative excess mortality from 1980 to 2015, specifically during the heatwave of 2003 (July 27 to August 15), and in future projections at 20-year intervals through 2100. Results The analysis revealed a significant rise in mortality risk at temperatures exceeding a minimum mortality temperature (MMT) of 19.0 °C, with an exponential trend and delayed effects lasting up to 5 days. The risk increased by 413% at the maximum extreme temperature of 36.6 °C. From 1980 to 2015, 2.32% of total deaths, equating to over 5,296 deaths, were heat-associated. No significant shifts over time were noted in the population’s response to heat. Future projections, without adaptation and demographic changes, show a potential increase in mortality by 15.88% under a “no mitigation policy” scenario by 2100, while mitigation measures could limit the rise to 6.61%. Conclusion Results underscore the urgent need for protective health policies to reduce regional population vulnerability and prevent premature heat-related deaths across the century.